Differentiation of human T-lymphoid leukemia cells into cells that have a suppressor phenotype is induced by phorbol 12-myristate 13-acetate. - Ryffel, B (1982)
Treatment of cultured human T-lymphoid (CEM) leukemia cells with nanomolar concentrations of phorbol 12-myristate 13-acetate (PMA) resulted in a reduction in cell growth and in the acquisition of a surface antigenic pattern that is common to both suppressor and cytotoxic T lymphocytes. This antigenic pattern was detected by OKT monoclonal antibodies. PMA treatment did not cause the expression of a cytotoxic function but rather induced the expression of a suppressor cell marker. This marker was characterized by the ability of the treated CEM cells to suppress [3H]thymidine incorporation into phytohemagglutinin-activated peripheral blood lymphocytes. After 4 days of treatment of CEM cells from either cloned or the parental cell population with 16 nM PMA, 71-98% of the cells expressed reactivity with OKT3 and OKT8 antibodies whereas reactivity with OKT4 and OKT6 was detected in less than or equal to 1-8% of the cells. The CEM cells can be divided into five groups based on the antigenic patterns of cells from randomly isolated clones. The cells from four of these groups were characterized by either low or high reactivity with each of the four OKT antibodies. The antigenic pattern of the fifth group resembled that of the parent CEM cells. The acquisition of reactivity with the OKT3 antibody in the CEM cells after PMA treatment was dependent on both time and dose and did not require cell replication. Acquisition of reactivity with OKT3 antibody also occurred after treatment with phorbol 12,13-dibutyrate but not after treatment with phorbol 13-monoacetate, phorbol 12,13-diacetate, or dimethyl sulfoxide. These results indicate that treatment of CEM cells with PMA and related agents can cause the cells to express a phenotype that resembles that of a mature suppressor T lymphocyte.